Innate and adaptive immunologic functions of complement in the host response to Listeria monocytogenes infection - Calame, Daniel G. (Immunobiology, 2016)
Listeria monocytogenes is a leading cause of foodborne-illness associated mortality that has attracted considerable attention in recent years due to several significant outbreaks. It has also served as a model organism for the study of intracellular pathogens. For these reasons the host response to L. monocytogenes has long been the subject of investigation. A potent innate and adaptive immune response is required for containment and clearance of L. monocytogenes. However, some elements of this response, such as type 1 interferons, can be detrimental to the host. Recent studies have revealed novel functions for the complement system, an ancient arm of innate immunity, in this process. Here we review the role of complement in the host response to L. monocytogenes.